Metallic Nanoparticles and Core-Shell Nanosystems in the Treatment, Diagnosis, and Prevention of Parasitic Diseases - Grzegorz Król; Kamila Fortunka; Michał Majchrzak; Ewelina Piktel; Paulina Paprocka; Angelika Mańkowska; Agata Lesiak; Maciej Karasiński; Agnieszka Strzelecka; Bonita Durnaś; Robert Bucki (Pathogens, 2023)
The usage of nanotechnology in the fight against parasitic diseases is in the early stages of development, but it brings hopes that this new field will provide a solution to target the early stages of parasitosis, compensate for the lack of vaccines for most parasitic diseases, and also provide new treatment options for diseases in which parasites show increased resistance to current drugs. The huge physicochemical diversity of nanomaterials developed so far, mainly for antibacterial and anti-cancer therapies, requires additional studies to determine their antiparasitic potential. When designing metallic nanoparticles (MeNPs) and specific nanosystems, such as complexes of MeNPs, with the shell of attached drugs, several physicochemical properties need to be considered. The most important are: size, shape, surface charge, type of surfactants that control their dispersion, and shell molecules that should assure specific molecular interaction with targeted molecules of parasites’ cells. Therefore, it can be expected that the development of antiparasitic drugs using strategies provided by nanotechnology and the use of nanomaterials for diagnostic purposes will soon provide new and effective methods of antiparasitic therapy and effective diagnostic tools that will improve the prevention and reduce the morbidity and mortality caused by these diseases.